Uncovering methylation-dependent genetic effects on regulatory element function in diverse genomes - Petersen, Rachel M.; Vockley, Christopher M.; Lea, Amanda J. (Genome Research, 2025)
A major goal in evolutionary biology and biomedicine is to understand the complex interactions between genetic variants, the epigenome, and gene expression. However, the causal relationships between these factors remain poorly understood. mSTARR-seq, a methylation-sensitive massively parallel reporter assay, is capable of identifying methylation-dependent regulatory activity at many thousands of genomic regions simultaneously and allows for the testing of causal relationships between DNA methylation and gene expression on a region-by-region basis. Here, we develop a multiplexed mSTARR-seq protocol to assay naturally occurring human genetic variation from 25 individuals from 10 localities in Europe and Africa. We identify 6957 regulatory elements in either the unmethylated or methylated state, and this set was enriched for enhancer and promoter chromatin annotations, as expected. The expression of 58% of these regulatory elements is modulated by methylation, which is generally associated with decreased transcription. Within our set of regulatory elements, we use allele-specific expression analyses to identify 8020 sites with genetic effects on gene regulation; further, we find that 42.3% of these genetic effects vary in direction or magnitude between methylated and unmethylated states. Sites exhibiting methylation-dependent genetic effects are enriched for GWAS and EWAS annotations, implicating them in human disease. Compared with data sets that assay DNA from a single European ancestry individual, our multiplexed assay is able to uncover more genetic effects and methylation-dependent genetic effects, highlighting the importance of including diverse genomes in assays that aim to understand gene regulatory processes.